Associations between clinical findings and MRI injury extent in male athletes with acute adductor injuries — A cross-sectional study. Issue 5 (May 2021) - Serner, Andreas; Hölmich, Per; Tol, Johannes L.; Thorborg, Kristian; Yamashiro, Eduardo; Weir, Adam
Abstract: Objectives: To investigate the association between clinical assessment and MRI measures of oedema and MRI grading in male athletes with acute adductor injuries. Design: Cross-sectional study. Methods: We included 81 consecutive athletes with acute adductor injuries. All athletes received a standardized clinical assessment and magnetic resonance imaging (MRI), blinded to clinical information. We analysed correlations between extent of palpation pain and extent of MRI oedema for the adductor longus. We compared the clinical assessment to MRI adductor injury grading (0−3) using ordinal regression. We analysed positive and negative predictive values (PPV/NPV) of a complete adductor longus avulsion. Results: Proximal-distal length of adductor longus palpation pain had fair correlation with MRI proximal-distal oedema length oedema (r = 0.309, p = 0.022). Cross-sectional surface area of palpation pain had poor correlation with corresponding cross-sectional MRI oedema area (r = 0.173, p = 0.208). The symptoms subscale of the Copenhagen Hip And Groin Outcome Score (HAGOS) for the period since injury (log odds ratio = 0.97, p = 0.021) and passive adductor stretch pain (log odds ratio = 0.35, p = 0.046) were associated with MRI injury grading. If there was a palpable defect, MRI always showed a complete avulsion (PPV = 100%). Several tests had high negative predictive values: passive adductor stretch (100%), palpation pain at the adductor longus insertion (98%), and the FABER test (98%). Conclusions: The extent of palpation pain does not indicate the extent of MRI oedema in acute adductor longus injuries. A worse modified HAGOS symptoms subscale score and passive adductor stretch pain indicate a higher MRI adductor injury grade. Clinical examination tests have high ability to detect or rule out a complete adductor longus avulsion on MRI.